DINAMIKA SOSIAL MASYARAKAT TERHADAP PENGGUNAAN JALAN UMUM:PERSPEKTIF MAX WEBER - Ahmad khairi Akbar; Agusmidah Agusmidah; Dedi Harianto (Journal of Innovative and Creativity, 2025)
This study examines the social dynamics of public road use using Max Weber's social action perspective. The regulation in Article 274 of Law Number 1 of 2023 is the main focus because it regulates the holding of parties or crowds on public roads without permission. This study uses a qualitative method based on library research, by reviewing legal and sociological literature to understand public behavior in public spaces. The results show that public road use is not only influenced by formal rules, but also by subjective meanings reflected in Weber's four types of social action: instrumental rational, value rational, affective, and traditional. Public roads are often used beyond their intended function, such as for private events or parties, which can disrupt road function, cause congestion, and even accidents. Legal regulations exist to regulate these dynamics, but their effectiveness depends on public social awareness. This study emphasizes that regulating public road use requires both a legal and sociological approach to create order, safety, and harmony in public spaces.